CREATIVE INDUSTRY HUMAN RESOURCES IN THE LEGAL FIELD TO THE INDUSTRIAL REVOLUTION 4.0 - Aryono Aryono; Indah Maulani; Rina Arum Prastyanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The technological revolution is now entering the fourth wave called the industrial revolution 4.0. Industry 4.0 is a technological revolution that gave birth to digital technology. The business world is undergoing a major transformation where most of the production processes shift from conventional technology to digital technology. Industry 4.0 transformation also provides benefits for industrial companies by increasing efficiency, improving machine and equipment performance, increasing the speed of production operations and product quality. The acceleration of digital transformation is a must to improve the manufacturing industry sector. Efforts to accelerate the transformation of industry 4.0 are to increase awareness and assist the industry in transforming. The formulation of the problem in this study is (1) how to develop Human Resources for innovation, in order to achieve organizational performance to meet the Industrial Revolution 4.0 in the legal field? (2) How has the acceleration of digital transformation become imperative to improve the manufacturing industry sector? The method research used is normative and descriptive. Keywords: Human Resources, Industrial Revolution 4.0, Technology